The effects of degassing, grain refinement & Sr-addition on melt quality-hot tear sensitivity relationships in cast A380 aluminum alloy. (August 2018) - Uludağ, Muhammet; Çetin, Remzi; Dispinar, Derya; Tiryakioğlu, Murat
Abstract: Hot tearing tendency of A380 with various element additions (Sr, Sr+Ti, Ti, B and B+Sr) was investigated. Constrained rod casting (CRC) hot tearing test method was used to characterize the hot tearing sensitivity. Reduced pressure test (RPT) samples were produced from each condition and all trials were repeated three times. Number density of pores on the cross section of RPT samples was calculated via digital image processing and statistical analysis was carried out. Microstructure analysis was carried out to observe the effect of alloying elements. Hot torn cross sections were subjected to SEM analysis. It was found that in aluminum alloys, the most deleterious defects, bifilms that are the cause of many defects, play an important role in initiating the hot tearing during solidification. It is important to note that the shape, size and distribution of bifilms are too complex. They act as heterogeneous nucleation site for liquid to separate and thus increase hot tearing. Graphical abstract: Highlights: Hot tear is a complex phenomenon. There is no single parameter that can be eradicated to be pin down as the source for hot tearing. Bifilms that are the cause of many defects, play an important role in initiating the hot tearing during solidification. Bifilm makes it more difficult to estimate whether a hot tearing can occur or not. Sr additions coupled with grain refining increases HTS. Best HTS is obtained in degassed melts with Al3B addition which was zero.